Vacuum instillation therapy in the treatment of purulent-necrotic forms of diabetic foot - N. N. Milica; V. V. Soldusova; V. V. Steblianko (Сучасні медичні технології)
Lack of control over the course of the disease (diabetes), ignoring measures to prevent the development of complicated forms of diabetic foot, late referral of patients with existing complications on the foot, contributes to an increase in the number of patients with destructive forms of diabetic foot.